Deed of Conveyance of the Quigrich by the Last Hereditary Keeper, with Consent of His Son, to the Society of Antiquaries of Scotland, for the National Museum - Dewar, Alexander; Dewar, Archibald (Proceedings of the Society of Antiquaries of Scotland, 1877)
A deed of conveyance transferring ownership of the Quigrich from Alexander Dewar to the Society of Antiquaries of Scotland, on the condition that it is deposited into the National Museum in Edinburgh.